Deconstructing the familiality of variability in momentary negative and positive affect. (20th August 2012) - Jacobs, N.; Menne‐Lothmann, C.; Derom, C.; Thiery, E.; van Os, J.; Wichers, M.
<x xml:space="preserve">Abstract</x> Objective: The daily life, affective phenotypes of momentary negative affect (NA), positive affect (PA) variability and NA variability are associated with future depressive symptomatology. This study investigates the extent to which genetic and environmental factors contribute to the inter‐individual differences in these daily life, affective phenotypes. Method: Two hundred and seventy‐nine female twins from the Flemish (Belgium) general population participated in an experience sampling study measuring affect in daily life. Structural equation modelling was used to fit univariate and bivariate models. Results: Genetic factors explained, respectively, 18%, 18% and 35% of the inter‐individual differences in momentary NA, PA variability and NA variability. Non‐shared environmental factors were found to explain the remaining inter‐individual variation. In addition, 41% of the association between positive and NA variability was attributed to shared genetic factors. Conclusion: Results of this study show that daily life patterns of affective expression are subject to substantial environmental influence. Prospective assessments of the effect of interventions on these expressions may therefore represent a powerful tool to prevent transition from subclinical depressive symptomatology to a clinical outcome or to reduce symptomatology in those with clinical depression.